Mass loading at the magnetopause through the plasmaspheric plume. Issue 10 (8th October 2016) - Wang, Yan; Tu, Jiannan; Song, Paul
Abstract: An investigation of the transport of the plasmaspheric plasma to the dayside magnetopause under disturbed geomagnetic conditions associated with plasmaspheric plumes is conducted by numerical simulations using the Dynamic Fluid‐Kinetic (DyFK) model. The simulations present the field‐aligned density distributions and kinetic features of multiple ion species (H + /He + /O + ) in a plasmaspheric flux tube that corotates while convecting toward the dayside magnetopause. The simulations show that the plasmaspheric plume can provide an equatorial magnetopause plasma density which is up to 3 orders of magnitude higher than that under the typical conditions. With the effects of wave‐particle interaction included, such mass loading through the plasmaspheric plume is even stronger. The local reconnection rate at the location where the plasmaspheric plume mass loads at the dayside magnetopause may decrease by 90%, depending on the geomagnetic activities, the outer plasmaspheric density, and the level and spatial span of the wave‐particle interaction. Key Points: The plasmaspheric plumes greatly enhance the equatorial magnetopause plasma density The higher density can be further enhanced by the wave‐particle interaction The dayside reconnection rate may be substantially reduced in association with the plumes